A comparative study of digital radiography, panoramic radiography, and computed tomography in dental implant procedures - Appaji Athota; Dara Balaji Gandhi Babu; Velpula Nagalaxmi; Shilpa Raghoji; Shefali Waghray; Chukka Rakesh Reddy (Wolters Kluwer Medknow Publications, 2017)
Introduction: The science of dental implantology has evolved exponentially in the recent past but the intricacies in the selection of implant site, size and angulations has always been challenging to the clinician and it is very difficult to meet these challenges without dental imageology. Aims: To compare panoramic radiography with computed tomography (CT) and radiovisiography to analyze the relative advantages and disadvantages of these modalities. Materials and Methods: Total 27 sites in 20 patients of mandibular posterior molar edentulous areas were radiographed with four different radiographic methods. The implant sites were selected and the height of the available bone, the mean width of the available crestal bone and density were measured using all the three techniques (except density which was measured on CT alone). Comparison of all the values obtained with the three imaging modalities was done and data tabulated for statistical analysis. The one way analysis of variance (ANOVA) with post hoc analysis using least significance method (LSD) was used to test the differences between each group using the SPSS software version 16. Results: The mean value of vertical measurements using conventional OPG, panoramic CT, RVG, and paraxial CT was found to be 19.32, 18.43, 19.09, and 16.81 mm, respectively. The mean value of density of the bone using paraxial CT was found to be 631.23 HU with a standard deviation of 123.14. The mean value of width of the crestal bone below the height of the crest using paraxial CT was found to be a maximum of 14.03 mm and a minimum of 5.86 mm. Conclusion: The overall results suggested that the paraxial view of CT was better in assessing the parameters of implant site when compared to the other three modalities.